1989
DOI: 10.1128/aac.33.8.1318
|View full text |Cite
|
Sign up to set email alerts
|

Cross-resistance to fluoroquinolones in multiple-antibiotic-resistant (Mar) Escherichia coli selected by tetracycline or chloramphenicol: decreased drug accumulation associated with membrane changes in addition to OmpF reduction

Abstract: Chromosomal multiple-antibiotic-resistant (Mar) mutants of Escherichia coli, selected on agar containing low concentrations of tetracycline or chloramphenicol, were 6-to 18-fold less susceptible to the fluoroquinolones than were their wild-type E. coli K-12 or E. coli C parental strains. The frequency of emergence of such mutants was at least 1,000-fold higher than that of those selected by the fluoroquinolone norfloxacin directly. When Mar mutants, but not wild-type cells, were plated on norfloxacin, mutants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
244
0
4

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(260 citation statements)
references
References 30 publications
12
244
0
4
Order By: Relevance
“…Such a pleiotropic mutation in a regulatory gene causing multi-drug resistance has been reported in mar mutants of E. coli (Cohen et al 1989(Cohen et al , 1993. In these mutants, both reduction of the outer membrane permeability and suppression of OmpF synthesis were observed, as in strain OW66 described in this study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Such a pleiotropic mutation in a regulatory gene causing multi-drug resistance has been reported in mar mutants of E. coli (Cohen et al 1989(Cohen et al , 1993. In these mutants, both reduction of the outer membrane permeability and suppression of OmpF synthesis were observed, as in strain OW66 described in this study.…”
Section: Discussionsupporting
confidence: 70%
“…It is known that permeability to antimicrobial agents, especially to small hydrophilic agents, through the outer membrane in E. coli greatly depends on the contents of OmpF and OmpC porin proteins, and that OmpF deficiency makes cells resistant to some antibiotics (Harder et al 1981;Cohen et al 1989;Ariza et al 1995;Thanassi et al 1995). The finding that the content of OmpF in strain OW66 was lower than that of strain OW6, even in the absence of CTAB, strongly suggests dependency of the resistance of the mutant on the OmpF level in the outer membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to antibiotics is not a known role for RpoS so the argument above-that mutations are less selected when RpoS is needed in stress resistance-does not hold readily. However, previous studies have shown that the major outer membrane porin through which chloramphenicol transverses in E. coli is OmpF (Harder et al 1981;Cohen et al 1988Cohen et al , 1989. RpoS negatively influences ompF transcription (Liu and Ferenci 2001); therefore loss of RpoS would be a disadvantage as high outer membrane permeability to antibiotics would be a liability and hence provide an indirect F sp contribution.…”
Section: Discussionmentioning
confidence: 98%
“…the presence of tetracycline in the environment), generally when the overproduction of the global activator protein MarA is induced (Hachler et al, 1991). In addition to the positive regulation of the acrAB operon, the MarA protein down-regulates the synthesis of the major porin OmpF, through the increased production of the antisense RNA, encoded by micF and that leads to the decreased accumulation of tetracycline (Cohen et al, 1988(Cohen et al, , 1989.…”
Section: Multidrug Transportersmentioning
confidence: 99%